Search for Trypanosoma Cruzi in Urban Bats and Dogs From Buenos Aires - Burgos, Juan Miguel (2023)
Chagas disease, the American trypanosomiasis, is caused by Trypanosoma cruzi infection. There are around 6 million of infected people in the endemic region of America. T. cruzi reservoir mammals are a fundamental component in the dynamics of infection establishment and spread. Domestic animals, as dogs, accompany humans in their movements, and it infection level is a demonstrated risk for transmission to human in endemic regions. Flying mammals, as bats, are reservoirs that can establish sources of infection thousands of kilometers away due to their migratory behavior. Herein, we analyzed 45 dogs and 75 bats (Tadarida brasiliensis) as putative parasite reservoirs captured in Buenos Aires city, not endemic for T. cruzi infection. Study was carried out by means of a new designed multiplex PCR (against sequences of T. cruzi satellite and mammal beta-actin) and the serologic trans-sialidase inhibition assay (TIA). Although our evaluations showed negative findings in all studied specimens, we stress the importance of maintaining epidemiological surveillance of companion animals that come from endemic regions, and of other mammals that can migrate thousands of kilometers, settling down out of endemic areas, where they can contribute to the installation of new cycles of infection.